City as Skin: Urban Imaginaries of Flesh and Fantasy. (November 2013) - Loeffler, Silvia; Mosley, Jonathan; Sara, Rachel
Abstract Like a human body patterned with tattoos, any city's public spaces are commonly covered with inscriptions. Artist and educator Silvia Loeffler describes how subversive and unauthorised interventions, such as graffiti, can be perceived as urban expressions of a 'sexscape' or body made of flesh, which emanate 'forms of longing and a dimension of the social'.